Effect of implant-abutment connection on direct impression accuracy with two impression materials - Kaveh Seyedan; Hasan Sazegara; Samira Sami Kermani; Mehdi Javan; Saghar Harandi (Isfahan University of Medical Sciences, 2010)
Introduction: One of the most important factors in long-term success of implant supported restorations is an accurate transfer of implant position by means of impression techniques. This study was designed to evaluate the effect of Implant Abutment Connection (IAC) on the accuracy of impression with different implant angulations and two different impression materials.Materials and Methods: A stainless steel model containing 10 implants (5 with external and 5 with internal connection) was fabricated with 0, 15, 30 and 40 degrees angulations. An open-tray impression technique was performed, using a custom tray and polyether (n = 30)/monophase polyvinyl siloxane (n = 30). The impressions were poured by stone type IV. The orientation of implants on the master models and the samples was evaluated by coordinating measuring machine (CMM) with 1 µm precision. Two-way analysis of variance and t-student test were used for statistical analysis via SPSS software. (α = 0.05)Results: No statistical differences were found between the two impression materials. There was also no significant difference between connection types in implants with 15˚and 30˚ angulations. However, 40˚ angulations showed higher degrees of error, using internal IAC.Conclusion: Types of connection along with implant angulations seem to have great impacts on impression precision. As observed, 40˚ implants with internal connection reduced impression precision. Key words: Impression accuracy, Implant angulation, Connection